Islam and Marxism in Ali Shariati’s Thoughts - Nabil, Ahmad Amir; Rahman, Tasnim Abdul (Universitas Islam Indonesia, 2024)
This paper discusses Ali Shariati's thinking and his intellectual background as an activist and catalyst for the rise and revolutionary consciousness of Iranian society that set in motion the Islamic revolution and its socio-political changes in 1979. The study is focused on his writings on Marxism. The method used in this study is a literature review with a conceptual and historical approach to text interpretation. The study's findings show the power of the dialectic formulated by Shariati in expressing the humanism and mysticism of Islam and its metaphysical views that reject the deviant views of atheism, communism, materialism and Marxism. His impressive political idealism emphasizes the moral and socio-religious strength of Islam in upholding the universal values of equality and principles of humanity and its spirit of liberation over the depravity and weakness of Marxist theory and its fundamental weakness in the moral and practical order